Uma ontologia para classificação de objetos de aprendizagem considerando o domínio cognitivo da taxonomia de bloom - Oliveira, Pablo Roberto Fernandes de (2018)
Virtual learning environments use learning objects as a learning resource to aid the teaching-learning process. In constructing a learning object, the teacher can establish an educational objective to assist in the evaluation of the student, and it is fundamental that the objectives of the course are well defined. Through Bloom's taxonomy, learning objects can have a well defined educational goal related to a level of cognitive learning. With the help of new technologies, the process of creating and managing learning objects from this perspective can be optimized by using the meta data semantics in data repositories of learning objects. However, for some contexts the metadata may prove to be insufficient in the semantical point of view to represent Bloom's taxonomy, and for the cases are use ontologies. In this way, this work presents an ontology for learning objects, considering the hierarchical levels of the cognitive domain of the Bloom taxonomy. The ontology allows the correct classification of the learning objects, considering the educational objectives, as well as the classification of the individuals that use learning objects in virtual learning environments. For the development of the ontology of this work, the Protegé tool was used, obeying the methodology proposed in guide 101. The ontology was validated using the FaCT ++ inference mechanism, using a hypothetical scenario, and later it was integrated into a virtual learning game to verify its application potential. A case study was applied with a group of pedagogues to evaluate the behavior of the ontology in said tool. Finally, through a questionnaire, the proposal was evaluated positively by the sample and it was concluded that the ontology behaved correctly in the classification of learning objects and in the classification of student learning